Effect of Seed Coating with Synthetic Polymer and Seed Treatment Chemicals on Seed Quality and Storability of Maize Hybrid Byrava super (Zea mays L.) - N NETHRA; K UMA RANI; RAME GOWDA; S NARAYANASWAMY (Seed Research, 2026)
Maintenance of seed vigour and viability during storage is a matter of prime concern. Research on storability of hybrid maize in India is of recent origin. Freshly harvested hybrid maize Byrava super seeds were given five treatments viz. polymer coating, flowable thiram, polymer + flowable thiram, vitavax 200, polymer + vitavax 200 and control. Then the polymer-coated seeds were shade dried and packed in gunny bag and HDPE inter woven non-laminated bag and stored under ambient condition for eight months. Bimonthly observations on seed quality parameters were recorded. At the end of eight months of storage, seeds treated with polykote + vitavax 200 seeds recorded the lowest seed moisture content (13.58%) with maximum germination (84%), seedling length (26.64 cm), vigour index-I (2057), vigour index II (4100) and field emergence (80%). The seeds stored in HDPE inter woven bags recorded the least moisture content with highest germination (79%), seedling length (25.71 cm), vigour index I (1987), vigour index II (3647) and field emergence (74%) compared to gunny bag. The study concluded that maize hybrid byrava super seeds coated with polykote @3ml/kg + vitavax 200@2g/kg stored in HDPE inter woven bag maintained the highest seed quality parameters up to eight months of storage.